Precocious cell differentiation occurs in proliferating cells in leaf primordia in Arabidopsis angustifolia3 mutant - Ezaki, Kazune; Koga, Hiroyuki; Takeda-Kamiya, Noriko; Toyooka, Kiminori; Higaki, Takumi; Sakamoto, Shingo; Tsukaya, Hirokazu (Frontiers in Plant Science, 2024)
During leaf development, the timing of transition from cell proliferation to expansion is an important factor in determining the final organ size. However, the regulatory system involved in this transition remains less understood. To get an insight into this system, we investigated the compensation phenomenon, in which the cell number decreases while the cell size increases in organs with determinate growth. Compensation is observed in several plant species suggesting coordination between cell proliferation and expansion. In this study, we examined an Arabidopsis mutant of ANGUSTIFOLIA 3 (AN3)/GRF-INTERACTING FACTOR 1, a positive regulator of cell proliferation, which exhibits the compensation. Though the AN3 role has been extensively investigated, the mechanism underlying excess cell expansion in the an3 mutant remains unknown. Focusing on the early stage of leaf development, we performed kinematic, cytological, biochemical, and transcriptome analyses, and found that the cell size had already increased during the proliferation phase, with active cell proliferation in the an3 mutant. Moreover, at this stage, chloroplasts, vacuoles, and xylem cells developed earlier than in the wild-type cells. Transcriptome data showed that photosynthetic activity and secondary cell wall biosynthesis were activated in an3 proliferating cells. These results indicated that precocious cell differentiation occurs in an3 cells. Therefore, we suggest a novel AN3 role in the suppression of cell expansion/differentiation during the cell proliferation phase.